The immune system is limited by oxidative stress: dietary selenium promotes optimal antioxidative status and greatest immune defense in pacu Piaractus mesopotamicus - Biller-Takahashi, Jaqueline D. [UNESP]; Takahashi, Leonardo S. [UNESP]; Mingatto, Fábio E. [UNESP]; Urbinati, Elisabeth C. [UNESP] (Elsevier B. V., 2015)
Reactive oxygen species (ROS) are reactive molecules containing oxygen, that form as byproducts of aerobic metabolism, including immune system processes. Too much ROS may cause oxidative stress. In this study, we examined whether it can also limit the production of immune system compounds. To assess the relationship between antioxidant status and immunity we evaluated the effect of dietary supplementation with organic selenium, given at various levels for 10 days, on the antioxidant and immune system of the pacu fish (Piaractus mesopotamicus). Fish fed a diet containing 0.6 mg Se-yeast kg(-1) showed significant improvement in antioxidant status, as well as in hematological and immunological profiles. Specifically, they had the highest counts for catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST), red blood cells, and thrombocytes; the highest leukocyte count (particularly for monocytes); and the highest serum lysozyme activity. There was also a positive correlation between GPx and lysozyme in this group of fish. These findings indicate that short-term supplementation with 0.6 mg Se-yeast kg(-1) reestablished the antioxidative status, allowing the production of innate components which can boost immunity without the risk of oxidative stress. This study shows a relationship between oxidative stress and immunity, and, from a practical perspective, shows that improving immunity and health in pacu through the administration of selenium could improve their growth performance.
Keywords: Antioxidant enzymes; Antioxidant status; Innate immunity; Trade-off